72 Can you trust on your patient? – the association between degree-of-worry vs self-rated health in acute illness. (16th April 2018) - Gamst-Jensen, H; Lippert, F; Folke, F; Thygesen, L
Abstract : Aim: Self-rated health (SRH) is strongly associated with mortality, 1 and acute hospitalisation in chronic illness. 2 An association between self-rated health and acute hospitalisation in injury and acute illness has not been shown. The 'degree-of-worry'-scale (DOW) has been shown to be associated with acute hospitalisation. 3 The study aimed to investigate the associations of SRH and DOW on acute hospitalisation in a population of callers to a medical helpline. Method: A prospective cohort study of 11 413 callers to a medical helpline between January 24 to February 9, 2017. Callers were asked to rate their health (1=excellent, 5=poor) and DOW (1=minimum worry, 5=maximum worry) before talking to a call-handler. Primary outcome was hospitalisation within 48 hours after first telephone contact, which was obtained from the National Patient Register. Logistic regression was performed. Results: A total of 11 305 callers with information on SRH and DOW were obtained of which 573 (5.1%) were hospitalised. Age-adjusted odds ratio for being hospitalised with a poor/bad SRH was 2.03 (95% CI: 1.64 to 2.53) and intermediate SRH 1.07 (95% CI: 0.81 to 1.4) compared with a good/excellent SRH. Callers with a high and intermediate DOW had an odds ratio of 4.78 (95% 3.6–6.34) and 2.1 (95% CI: 1.54 to 2.85) compared with a low DOW for hospitalisation. Adjusting for age did not change the estimates. Conclusion: DOW has a stronger association to acute hospitalisation in injury, illness and exacerbation of chronic illness than SRH. Asking about DOW could improve guidance to the dynamic process of decision-making. References: . Idler EL, Benyamini Y. Self-rated health and mortality: A review of twenty-seven community studies. J Health Soc Behav1997;38(1):21–37. . Farkas J, Kosnik M, Flezar M, Suskovic S, Lainscak M. Self-rated health predicts acute exacerbations and hospitalizations in patients with COPD. Chest2010;138(2):323–30. . Gamst-Jensen H, et al. Self-rated worry predicts hospitalisation in out-of-hours services telephone triage . Emergency medical Services, Copenhagen, Denmark; 2018 (abstract, not published). Conflict of interest: None Funding: Trygfonden, Danish Nurses Association and Laerdal Fonden.